Daya Hasil 12 Hibrida Harapan Jagung Manis (Zea maysL. var. saccharata) di Kabupaten Maros, Sulawesi Selatan - Hesti Paramita Sari; . Suwarto; Muhamad Syukur (Buletin Agrohorti, 2013)
The objective of this research was to evaluate yield potential of 12 sweet corn promising hybrids from Plant    Breeding Program (Bogor Agricultural University) and Indonesian Cereals Research Institute colection. This research was conducted at experimental field Indonesian Cereals Research Institute, in Maros, South Sulawesi, from June to August 2011. The genotypes used were : IM-12, IM-13, IM-14, IM-15, IM-16, IM-23, IM-24, IM-25, IM-34, IM-35, IM-45, IM-55, and three comercial varieties i.e. Super Sweet Corn, Sweet Boy, and Talenta. The design of this research was Randomized Complete Block Design with four replications. Data was analyzed with F-test then continued with Dunnett test (α=5%). Selection index was used for choosing the best genotype. Interaction between two factors, i.e. genotype and year, was analyzed with combined variance analysis using primary data from this research and secondary data from last year research (done from April to June 2010). Broad sense heritability was estimated from this two-factors analysis. The result from this research was the sweet corn productivity was not affected by genotype, but affected by genotype and year interaction. On the other hand, total soluble solid was affected by genotype, but not affected by interaction between genotype and year. Among characters evaluated, total soluble solid had highest broad sense heritability. Based on selection index, IM-16 was a promising hybrid and can be developed to be new commercial variety.Keywords: yield trial, sweet corn hybrid, selection index, broad sense heritability